A multiple species, continent-wide, million-phenotype agronomic plant dataset - Saul Justin Newman (Nature Portfolio, 2021)
Measurement(s) grain yield trait • protein content • days to flowering trait • Glucosinolate • plant structure development stage Technology Type(s) specimen harvest quantity • Mass Spectrometry • agronomic process Sample Characteristic - Organism Pisum sativum • Secale cereale x Triticum aestivum • Triticum aestivum • Brassica napus • Avena sativa • Lens culinaris • Cicer arietinum • Lupinus angustifolius • Vicia faba Sample Characteristic - Environment cultivated environment Sample Characteristic - Location Australia Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13709956